Experimental Substantiation of Taurine Use in Prophylaxis of Isoniazid-Induced Neurotoxic Reactions - G. N. Mozhokina; N. A. Elistratova (Антибиотики и Химиотерапия)
The effect of taurine and vitamin B6 on the clinical process and mortality of experimental mice due to isoniazid was studied in an acute test. The use of taurine lowered the toxic effect of isoniazid, evident from delayed covulsions, their shorter time, rarer repeat and lower mortality of the animals due to tonoclonic spasm. The most significant decrease of the neurotoxic effect of isoniazid was observed with the use of taurine in a dose of 255 mg/kg. When taurine in the dose of 255 mg/kg was used in combination with vitamin B6 in prophylactic doses of 1.3 or 3.9 mg/kg, no death of the mice due to isoniazid in the acute test was recorded.